The Challenges Faced by Teachers in Developing Literary Literacy Among Senior High School Students in Sungai Penuh City Under the Merdeka Curriculum: TANTANGAN GURU DALAM MENGEMBANGKAN LITERASI SASTRA SISWA SMA KOTA SUNGAI PENUH PADA KURIKULUM MERDEKA - Ardi, Ririn Lovenia; Syofiani, Syofiani; Azkiya, Hidayati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe the challenges faced by Indonesian language teachers in developing literary literacy among senior high school students in Sungai Penuh City during the implementation of the Merdeka Curriculum. The study employed a quantitative approach using a survey method. Data were collected through a Google Form–based questionnaire distributed to Indonesian language teachers at the senior high school level. The research instrument was designed using a Likert scale to capture teachers’ perceptions of the implementation of literary literacy in schools. The findings indicate that teachers encounter several major challenges in developing literary literacy, including limited instructional time, teachers’ readiness to design creative and contextual literary learning, students’ low interest in reading literary works, and limited availability of literary teaching materials. Limited instructional time emerged as the most dominant challenge, followed by teachers’ need for training and mentoring in implementing the Merdeka Curriculum. These findings suggest that the development of literary literacy within the Merdeka Curriculum requires sustained support, including the enhancement of teachers’ competencies, the provision of relevant teaching materials, and the adoption of instructional strategies that can increase students’ interest and engagement. This study is expected to contribute to the development of literary learning at the secondary school level.